(untitled) (The Science Post, 2025)
Sustainability has emerged as a critical consideration in contemporary project management, demanding the integration of environmental, social, and economic objectives alongside traditional performance metrics. This paper presents a structured framework for embedding sustainability principles into all phases of the project life cycle. The methodology combines a comprehensive literature review, framework development, expert validation through the Delphi method, and application to a renewable energy infrastructure case study. Key sustainability indicators—such as carbon footprint reduction, resource efficiency, stakeholder inclusiveness, and life cycle cost analysis —were aligned with project deliverables to ensure measurable impact. Findings demonstrate that applying the framework led to a 27% reduction in carbon emissions, improved resource efficiency by up to 24%, increased stakeholder engagement by 31%, and reduced long-term operational costs by 15%. The results confirm that integrating sustainability objectives early in project planning significantly enhances overall project performance and long-term value creation. The proposed framework offers a practical, adaptable approach for organizations seeking to align project management practices with global sustainability goals, while also achieving operational and financial benefits.